2010
DOI: 10.1038/onc.2010.25
|View full text |Cite
|
Sign up to set email alerts
|

Substrate stiffness and the receptor-type tyrosine-protein phosphatase alpha regulate spreading of colon cancer cells through cytoskeletal contractility

Abstract: Microenvironmental clues are critical to cell behavior. One of the key elements of migration is the generation and response to forces. Up to now, there is no definitive concept on how the generation and responses to cellular forces influence cancer-cell behavior. Here, we show that expression of receptor-type tyrosine-protein phosphatase alpha (RPTPa) in human SW480 colon cancer cells sets a threshold for the response to matrix forces by changing cellular contractility. This can be explained as an RPTPamediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 33 publications
(47 reference statements)
3
41
0
Order By: Relevance
“…Junctional integrity requires cortical actomyosin contractility, which is promoted by E-cadherin homophilic binding and contributes to the extension and strengthening of E-cadherin-based adhesions, by generating tension along the junctions . RPTPa has already been linked to cytoskeletal contractility and stress fiber formation at integrin-based focal adhesion sites; these effects depend on substrate stiffness and require RPTPa-mediated SFK activation (Krndija et al, 2010;von Wichert et al, 2003;Zeng et al, 2003). Our observation of reduced junctional linearity in epithelial monolayers as a consequence of RPTPa knockdown suggests that there is imbalanced junctional tension between adjacent cells.…”
Section: Functions Of Rptpa At the Epithelial Junctionsmentioning
confidence: 54%
See 1 more Smart Citation
“…Junctional integrity requires cortical actomyosin contractility, which is promoted by E-cadherin homophilic binding and contributes to the extension and strengthening of E-cadherin-based adhesions, by generating tension along the junctions . RPTPa has already been linked to cytoskeletal contractility and stress fiber formation at integrin-based focal adhesion sites; these effects depend on substrate stiffness and require RPTPa-mediated SFK activation (Krndija et al, 2010;von Wichert et al, 2003;Zeng et al, 2003). Our observation of reduced junctional linearity in epithelial monolayers as a consequence of RPTPa knockdown suggests that there is imbalanced junctional tension between adjacent cells.…”
Section: Functions Of Rptpa At the Epithelial Junctionsmentioning
confidence: 54%
“…Overexpression of RPTPa can induce fibroblast transformation, presumably through its Src-activating activity (Tremper-Wells et al, 2010; Zheng et al, 1992). Although in vitro and in vivo observations indicate that RPTPa can also control carcinoma tumorigenesis and/ or invasiveness (Ardini et al, 2000;Huang et al, 2011;Krndija et al, 2010;Meyer et al, 2013), its cell biological function in the epithelial context has hardly been investigated. Identifying RPTPa as a mediator of E-cadherin-dependent c-Src activation provides new insight into the relevance of receptor PTPs for the properties of normal and neoplastic epithelia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that integrins affect the rigidity of the ECM, possibly by regulating lox mRNA expression. Thus, matrix rigidity often correlates with malignancy, suggesting more general implications of matrix rigidity and cell migration (Krndija et al, 2010;Paszek et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Some other reports have demonstrated the presence of differential regulatory effects in Rho-kinase and MLCK. The receptor-type tyrosine-protein phosphatase (RPTPalpha)-mediated increase in the number and size of focal adhesion and stress fibres is dependent on the MLCK activity, but not on the activity of Rhokinase [37]. On the other hand, extracellular stiffness influences both the expression and the activity level of RhoA/Rho-kinase-mediated contraction-associated proteins [38].…”
Section: Introductionmentioning
confidence: 99%